Persoonsbeelde van 'n groep manlike jeugoortreders : 'n pedagogies-kliniese ondersoek - Du Toit, J. H.(Johan Hablutzel) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ed.) -- Universiteit van Stellenbosch, 1966.